Organized Crime in the Trade of Endangered Fauna: A Study of Environmental Law and Criminal Law Policies and Their Enforcement in Indonesia - Agus, Agus; Aditiarman, Aditiarman (Jurnal Sosial, Sains, Terapan dan Riset (Sosateris), 2025)
This study examines the environmental and criminal law policies in force in Indonesia, as well as the effectiveness of law enforcement in dealing with organized crime related to the trade in endangered fauna. Although existing regulations such as Law Number 5 of 1990 concerning Conservation of Natural Resources and Ecosystems and Law Number 32 of 2009 concerning Protection and Management of the Environment have regulated the protection of endangered fauna, this study found that its implementation in the field still faces various challenges, including weak coordination between law enforcement agencies, lack of human resources and technology, and limitations in enforcing criminal sanctions. Using the “deterrence theory” and “collaborative governance theory” approaches, this study analyzes how criminal sanctions and cross-sectoral cooperation can improve the effectiveness of law enforcement against organized crime. The results of the study show that although the criminal sanctions regulated are quite strict, their effectiveness is still weak due to the lack of certainty of enforcement and low collaboration between agencies. This study also highlights the importance of the role of local communities (Customary Institutions) and monitoring technology to support efforts to conserve endangered fauna in the TNKS area. This study provides strategic recommendations to strengthen law enforcement through increased inter-agency coordination, the use of more sophisticated monitoring technology, and expanding international cooperation to address organized crime networks operating across borders.